2019
DOI: 10.3390/w11051019
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Runoff and Sediment Yields Under Different Crop and Tillage Conditions by Field Artificial Rainfall Experiments

Abstract: Crop types and tillage measures on slopes have significant impacts on regional water and soil conservation. In this study, we investigated the influences of multiple crop types and tillage measures on water and sediment yields based on plot-scale experiments under artificial rainfall. The objective of the study is to find the best combination of crop type and tillage measure from the perspective of reducing soil erosion. We performed artificial rainfall experiments under eight slope treatments, which are the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Globally, changes in land use and management practices accelerated soil erosion and have led to irrevocable land degradation, which is affecting 23.5% of the earth's land area [12,13]. Soil erosion is one of the serious problems which not only impair the quality of land and water resources but also harm agricultural production and the socio-economic condition of farmers.…”
Section: The Extent Of Land Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, changes in land use and management practices accelerated soil erosion and have led to irrevocable land degradation, which is affecting 23.5% of the earth's land area [12,13]. Soil erosion is one of the serious problems which not only impair the quality of land and water resources but also harm agricultural production and the socio-economic condition of farmers.…”
Section: The Extent Of Land Degradationmentioning
confidence: 99%
“…Higher soil erosion results in the removal of fertile topsoil along with nutrients which leads to reduced agronomic yield, land degradation, and terrain deformation [25][26][27]. The main causal factors affecting the rate of soil erosion are parent material, soil texture, slope steepness, plant cover, tillage, and climate [13]. According to an estimate of existing soil loss data, the mean annual rate of soil erosion in our country is approximately 16.4 ton ha −1 which results in annual total soil loss of 5334 million tons (m t) and nutrient loss of 8.4 m t throughout the country [17].…”
Section: Impact Of Soil Erosion On Agriculturementioning
confidence: 99%
“…And this is related to the reduced runoff discharge that reduced from 5.32 L to 0.96 L (Figure 8). Many authors consider Tillage as a threat to the sustainability of the agriculture land due to the high erosion rates induced [60,61]. Novara et al [62] measured 9.5 Mg ha −1 y −1 and considered that the Sicilian vineyards are under an environmental problem.…”
Section: Discussionmentioning
confidence: 99%
“…Soil erosion is higher in the tilled soils due to the loss of vegetation cover that contributes to a more efficient raindrop impact such as Fernández Raga et al [71] or Marzen et al [72] found in their researches. The contribution of the raindrop impact and the splash detachment is negligible when Many authors consider Tillage as a threat to the sustainability of the agriculture land due to the high erosion rates induced [60,61]. Novara et al [62] [63,64] in Germany and Spain.…”
Section: Discussionmentioning
confidence: 99%
“…We must protect soil as one part of the earth's ecosystem, especially in the future, due to environmental changes, because soil plays a key role in the production of agricultural crops and subsequently food (an important factor in maintaining food quality and safety, human health and the sustainability of entire ecosystems) [14,19,20]. The conditions of agricultural production have changed drastically (reduction of human labour, inappropriate crop rotation, reduced livestock production, low manure production and thus the supply of organic matter into the soil and dependence on the mineral nitrogen) [21,22].…”
Section: Introductionmentioning
confidence: 99%